Instructional Approaches and Student Creativity as Separate Determinants of Mathematics Learning Outcomes: Findings from a Factorial Quasi-Experimental Study - Wahyu Kusumaningtyas; Yunita Widya Putri; Riski Rusmalinda (Journal of Transdisiplinary Studies in Education, 2025)
Background: Differences in students’ creative capacities are often overlooked in mathematics instruction, even though they may influence how learners respond to various teaching approaches. As a result, the specific contribution of instructional approaches and creativity to mathematics learning outcomes has not been sufficiently clarified. Aims: This study seeks to investigate the influence of instructional approaches and student creativity levels on mathematics learning outcomes and to explore whether these factors interact in shaping students’ achievement. Methods: A quasi-experimental study was conducted using a 2×3 factorial design. Seventh-grade students were selected through cluster random sampling. Mathematics achievement was measured using a standardized test, while student creativity was assessed through a questionnaire. Data normality and homogeneity were examined before applying a two-way analysis of variance with unequal cell sizes. Result: The analysis reveals that instructional approaches significantly affect mathematics learning outcomes, with students exposed to contextual cooperative instruction achieving higher scores than those receiving direct instruction. Creativity levels also show a significant influence, as students with higher creativity consistently demonstrate better learning outcomes. However, the interaction between instructional approaches and creativity levels is not statistically significant. Conclusion: These findings indicate that instructional approaches and student creativity independently contribute to mathematics learning outcomes. Therefore, improving achievement requires both the use of effective teaching approaches and sustained efforts to develop students’ creative capacities, rather than relying on their combined interaction.